2016
DOI: 10.1080/10428194.2016.1267349
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic and renal improvement of monoclonal immunoglobulin deposition disease after treatment with bortezomib-based regimens

Abstract: Monoclonal immunoglobulin deposition disease (MIDD) is characterized by non-organized immunoglobulin-fragments along renal basement membranes with subsequent organ deterioration. Treatment is directed against the immunoglobulin-producing clone. We treated 18 MIDD patients with bortezomib-based regimens (12 received bortezomib-dexamethasone, 6 bortezomib-dexamethasone with cyclophosphamide). Eleven (61%) patients achieved a hematologic response, but only 6 (33.3%) reached to a complete (CR) or very good partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
1
13
0
11
Order By: Relevance
“…Similarly, although there was no effect of bortezomibbased therapy on RS detected, improved RS following bortezomib has previously been observed in other MGRS studies (Cohen et al, 2015;Sayed et al, 2015;Li et al, 2016;Chauvet et al, 2017;Ziogas et al, 2017). This may be explained by the confounding effect of CKD stage, because patients with more advanced kidney disease at diagnosis were more likely to receive clone-directed treatment at an earlier time point along their disease course.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, although there was no effect of bortezomibbased therapy on RS detected, improved RS following bortezomib has previously been observed in other MGRS studies (Cohen et al, 2015;Sayed et al, 2015;Li et al, 2016;Chauvet et al, 2017;Ziogas et al, 2017). This may be explained by the confounding effect of CKD stage, because patients with more advanced kidney disease at diagnosis were more likely to receive clone-directed treatment at an earlier time point along their disease course.…”
Section: Discussionmentioning
confidence: 62%
“…Признание зарубежными медицинскими сообществами, в том числе Международной рабочей группой по миеломе (International Myeloma Working Group) [18], взаимосвязи клона и поражения почек -моноклональной гаммапатии ренального значения -открыло возможность назначения таким пациентам высокоэффективной химиотерапии. Терапевтическое воздействие, направленное на подавление клона, оказалось эффективным как в отношении почечных исходов, так и общей выживаемости [7,9,[12][13][14].…”
Section: обоснование необходимости введения нозологической группы монunclassified
“…Fortunately, the hematologic response can be improved by the addition of autologous stem cell transplant. Achievement of VGPR in monoclonal Ig deposition disease similarly has been found to improve renal and patient survival (21,42,74,89). Kidney transplant has been successfully performed in patients with hematologic complete response without recurrence.…”
Section: Managementmentioning
confidence: 99%
“…Patients with complete response are less likely to have recurrence after kidney transplant (88). Bortezomib seems to be the most effective agent in monoclonal Ig deposition disease (21,42,74,89). In one study, immunomodulatory drugs represented by thalidomide and lenalidomide were found to be less effective in achieving VGPR or better responses (21).…”
Section: Managementmentioning
confidence: 99%